Robert C. Taylor report - Taylor, Richard C. (Richard Cowling), 1789-1851.
Report on minerals in Tioga County, Pa.
Positive photocopy.
Geologist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Mines and mineral resources -- Pennsylvania -- Tioga County; Geologists